The Potential of Sun-Dried Grape Pomace as a Multi-Functional Ingredient for Herbal Infusion: Effects of Brewing Parameters on Composition and Bioactivity - Vlasios Goulas; Konstantina Stavrou; Christodoulos Michael; George Botsaris; Alexandra Barbouti (MDPI AG, 2021)
Wine and by-products are essential elements of a Mediterranean diet and considered as a reservoir of bioactive compounds with various health effects. Grape pomace, an easily available natural material of low cost, shares a similar wealth of health benefiting bioactive phytochemicals. The objective of this study was to explore the utilization of grape pomace from Commandaria dessert wine as main ingredient for functional infusions. Therefore, the ratio of water to grape pomace powder (40-200 mL g−1), infusion time (3-15 min) and temperature (55-95 °C) were optimized in terms of composition and bioactivity. Multiple response optimization indicated that brewing 200 mL water per g of material for 12.2 min at 95 °C, was the optimum method for preparing the infusion. Results also revealed a significant impact of three parameters as well as quadratic and interactive effects on composition and bioactivity of infusions. Furthermore, the infusion presents antimicrobial effects against Listeria monocytogenes serotypes and other common food pathogenic bacteria. Finally, a sensory evaluation was performed to assess the organoleptic attributes of the infusion and its improvement, with the addition of Mediterranean aromatic plants. Overall, the present work describes a promising strategy for the re-use of sun-dried grape pomace as a functional ingredient of infusions.